The empathic civilization the race to global consciousness in a world in crisis - Rifkin, Jeremy (New York J.P. Tarcher/Penguin, 2009)
Bestselling social critic Jeremy Rifkin shows that the disconnection between our vision for the world and our ability to realize that vision lies in the current state of human consciousness.
The hidden paradox of human history -- The new view of human nature -- A sentient interpretation of biological evolution -- Becoming human -- Rethinking the meaning of the human journey -- The ancient theological brain and patriarchal economy -- Cosmopolitan Rome and the rise of urban Christianity -- The soft industrial revolution of the late medieval era and the birth of humanism -- Ideological thinking in a modern market economy -- Psychological consciousness in a postmodern existential world -- The climb to global peak empathy -- The planetary entropic abyss -- The emerging era of distributed capitalism -- The theatrical self in an improvisational society -- Biosphere consciousness in a climax economy.
Includes bibliographical references (p. [643]-656) and index.
Keywords: Empathy; Conduct of life; Civilization, Modern -- 21st century -- Forecasting; Twenty-first century -- Forecasts; Social prediction